Microbial alterations of oral cavity and their association with Pancreatic Cancer - Radziejowska, Zuzanna; Bielak, Alicja; Gryta, Jakub; Iwan, Karolina; Janczewska, Martyna; Kalicka, Maria; Krysa, Tomasz; Kolasa, Agata; Szklarz, Magdalena (Quality in Sport, 2023)
Introduction: Pancreatic Cancer (PC), while relatively infrequent, remains one of the deadliest cancers as a result of late diagnosis and absence of preventive measures. Over 50 % of patients diagnosed with PC already suffer metastasis. Combined with lack of effective treatment, the need arises for universal biomarkers specific to PC. In the last decades the importance of human microbiota in its upholding of the body homeostasis has been under radar, in special regards to its association to cancer. Several species of oral microbiome have been linked to increased or decreased risk of developing pancreatic cancer, most notably P.gingivalis and Fusobacteria. Purpose of the study: The aim of this study is to collect and summarize existing evidence on connection of oral microbiome and pancreatic cancer, as well as to assess their potential use in diagnostics of PC . Material and method: Literature review was performed, in English databases, using keywords : cancer, pancreatic cancer, pancreatic cancer prevention, oral microbiome, microbe variation, microbial biomarkers. Results and conclusions: In our systematic review, evident differences between microbial architecture of PC patients and healthy individuals were observed. The data on association between microbiota and risk of developing cancer is limited, however it still provides evidence for relationship between microbial composition and incidence of pancreatic cancer.